A critical hybrid realist-outcomes systematic review of relationships between medical education programmes and communities: BEME Guide No. 35. (3rd March 2016) - Ellaway, R. H.; O'Gorman, L.; Strasser, R.; Marsh, D. C.; Graves, L.; Fink, P.; Cervin, C.
Abstract: Background : The relationships between medical schools and communities have long inspired and troubled medical education programmes. Successive models of community-oriented, community-based and community-engaged medical education have promised much and delivered to varying degrees. A two-armed realist systematic review was undertaken to explore and synthesize the evidence on medical school–community relationships. Method : One arm used standard outcomes criteria (Kirkpatrick levels), the other a realist approach seeking out the underlying contexts, mechanisms and outcomes. 38 reviewers completed 489 realist reviews and 271 outcomes reviews; 334 articles were reviewed in the realist arm and 181 in the outcomes arm. Analyses were based on: descriptive statistics on both articles and reviews; the outcomes involved; the quality of the evidence presented; realist contexts, mechanisms, and outcomes; and an analysis of underlying discursive themes. Findings : The literature on medical school–community relationships is heterogeneous and largely idiographic, with no common standards for what a community is, who represents communities, what a relationship is based on, or whose needs are or should be being addressed or considered. Conclusions : Community relationships can benefit medical education, even if it is not always clear why or how. There is much opportunity to improve the quality and precision of scholarship in this area.